PENGARUH KUALITAS RUANG DAN PERSEPSI PENGUNJUNG TERHADAP KEBERLANGSUNGAN RUANG PUBLIK Studi Kasus: Taman Kota Lapang Bhakti Kota Banjar - Stefy Prasasti Anggraini (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2022)
Abstract: Taman Kota Lapang Bhakti is one of the public spaces in the city of Banjar whose function is quite vital. There is a placemaking phenomenon in this city park, where the southern area of the city park which is a commercial area is no longer operational at all, while the northern area which has the same function is still operational today. This study discusses in depth to find out the causes of this phenomenon. This phenomenon is studied with the theory of placemaking and space quality. The research method used is descriptive qualitative method by comparing the quality of space and visitors' perceptions of the northern and southern areas of the city park. While the data collection methods are in the form of observation, literature study, and interviews with visitors and management of this city park. Research findings based on an interview survey, 82.4% of visitors prefer to visit the northern commercial area compared to the southern area. This is due to several factors in their perception related to connectivity, activity, image and comfort. This factor also proves that the quality of space and the perception of visitors affect the sustainability of a public space. The recommendation from this problem is to make the southern area a special community area with non-commercial functions.Keywords: space quality, perception, placemaking, public area